The betrayal of East Pakistan - Niazi, Amir Abdullah Khan. (New Delhi : Manohar, 1998)
Chiefly an account of events leading to the birth of Bangladesh.
Includes index.
Keywords: Niazi, Amir Abdullah Khan; India-Pakistan Conflict, 1971 -- Personal narratives, Pakistani; Bangladesh -- History -- Revolution, 1971 -- Personal narratives, Pakistani